2013
DOI: 10.1111/bph.12035
|View full text |Cite
|
Sign up to set email alerts
|

The sphingosine kinase inhibitor 2‐(p‐hyroxyanilino)‐4‐(p‐chlorophenyl)thiazole reduces androgen receptor expression via an oxidative stress‐dependent mechanism

Abstract: BACKGROUND AND PURPOSESphingosine kinase catalyses the formation of sphingosine 1-phosphate and is linked with androgen receptor signalling in prostate cancer cells. Therefore, we investigated the effect of sphingosine kinase inhibitors on androgen receptor expression. EXPERIMENTAL APPROACHAndrogen-sensitive LNCaP cells were treated with SKi (2-(p-hydroxyanilino)-4-(p-chlorophenyl)thiazole), which inhibits sphingosine kinases 1 and 2 activity, and the effect on androgen receptor expression was measured. KEY RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…There were three putative thiamine biosynthesis proteins induced by the above stresses (Table 1), vitamin B1 (thiamine) is a player during plant adaptation to stresses, mainly oxidative stress [75,76]. Our results also showed that chlororespiratory reduction 3 (CRR3) [77], thiazole biosynthetic enzyme, the precursor of vitamin B1[78], G. hirsutum alcohol dehydrogenase 1 (ADH1) [79], PAP (Plastid-lipid associated protein) fibrillin, MAR-binding filament-like protein 1 (MFP1) [80], NDH-dependent cyclic electron flow 1, protein like Starch Excess 4 (SEX4) 1 [81], SAP domain-containing protein, phenylalanine ammonia-lyase 1 (PAL1) were commonly up-regulated.…”
Section: Resultsmentioning
confidence: 84%
“…There were three putative thiamine biosynthesis proteins induced by the above stresses (Table 1), vitamin B1 (thiamine) is a player during plant adaptation to stresses, mainly oxidative stress [75,76]. Our results also showed that chlororespiratory reduction 3 (CRR3) [77], thiazole biosynthetic enzyme, the precursor of vitamin B1[78], G. hirsutum alcohol dehydrogenase 1 (ADH1) [79], PAP (Plastid-lipid associated protein) fibrillin, MAR-binding filament-like protein 1 (MFP1) [80], NDH-dependent cyclic electron flow 1, protein like Starch Excess 4 (SEX4) 1 [81], SAP domain-containing protein, phenylalanine ammonia-lyase 1 (PAL1) were commonly up-regulated.…”
Section: Resultsmentioning
confidence: 84%
“…The dual sphingosine kinase inhibitor SKI-II also diminishes AR expression independent of apoptotic or autophagy signaling (38). Since exogenous S1P was unable to restore AR expression, a role for intracellular S1P was implicated (38). Nuclear localization of both SPHK2 and the AR suggests the possibility that the SPHK2-derived pool of S1P could be important for its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear localization of both SPHK2 and the AR suggests the possibility that the SPHK2-derived pool of S1P could be important for its expression. However, at 10 μM the SPHK2-specific inhibitor (R)-FTY720 methyl ether (ROME) failed to decrease AR expression and decreases at 50μM were thought to occur as a consequence of an off-target effect (38). Future studies using RNAi approaches will be needed to mechanistically investigate the relationship between sphingosine kinases and AR expression.…”
Section: Discussionmentioning
confidence: 99%
“…SKI II is a nonstructural analog of Des1 substrate and, as such, it does not probably directly interact with the Des1 protein. SKI II has been reported to induce oxidative stress ( 76 ), and so its activity as a Des1 inhibitor may result from its activity at modifying the redox status of cells. However, the occurrence of inhibition in cell lysates is against the involvement of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%